What Drives Educational Support for Children With Developmental Language Disorder or Autism Spectrum Disorder: Needs, or Diagnostic Category? - Dockrell, Julie E.; Ricketts, Jessie; Palikara, Olympia; Charman, Tony; Lindsay, Geoff A. (Frontiers in Education, 2019)
A central conceptual change in the Warnock report, the first type report of a UK government committee on the education of children and young people with all types of special educational needs (Department for Education and Science, 1978), was the shift from categorization of children and young people by handicap to the identification of individuals' special educational needs (SEN). However, the focus on categories has persisted. In this paper we examine the relationship between the educational provision made for children with SEN in relation to diagnostic categories as opposed to assessed needs. We draw on data from one of the studies in the Better Communication Research Programme which was commissioned by the UK government in response to the Bercow Review (2008) into provision for children and young people with speech, language and communication needs. Data were collected from 74 mainstream schools in England about the support provided to two groups of children with identified SEN (N = 157, Mean age 10;2 years): those with developmental language disorder (DLD) n = 93 and those with autism spectrum disorder (ASD) n = 64. Information was collected about school support and support by external professionals (speech and language therapists (SLTs), educational psychologists and other support services). The type and level of support provided was examined and the ways in which these differed between children with a diagnosis of DLD or ASD explored. We considered whether the support provided varied according to within child or contextual factors. In addition, change in the provision made over a 2 year time period was examined. To our knowledge this is the first study to concurrently recruit pupils with DLD and ASD from the same mainstream settings to examine differences and similarities in their profiles and the ways in which these impact on service delivery. The results demonstrated provision for children with DLD and ASD continues to be driven by diagnostic categories, and that children with ASD are significantly more likely to receive support from schools and SLTs, independent of children's language, literacy, cognitive scores and behavior. Driving amount of provision by diagnostic category limits the possibility of providing effective provision to meet the children's individual language and learning needs. This raises serious questions about the allocation of support resources and, by corollary, indicates the likelihood currently of an inequitable allocation of support to children and young people with DLD.